Blind multiuser receiver for space-time coded CDMA signals in frequency-selective channels. - Tugnait, J.K (IEEE Transactions on wireless communications)
Blind detection of a desired user's signal in a direct sequence code-division multiple-access (DS-CDMA) system using multiple transmit and receive antennas and space-time (ST) block coding is considered. We consider Alamouti's ST coding scheme for two transmit antennas designed for flat-fading channels but allow the channel to be frequency selective. A (spreading) code-constrained inverse filter criterion (IFC)-based linear blind detector to detect a desired user's signal for uncoded CDMA signals exploiting only a single transmit and single receive antenna was recently presented. The IFC method exploits the higher order statistics of the data. In ST-coded multiantenna CDMA systems, a user signal may be treated as the superposition of several virtual user signals derived from the same parent user. In particular, for Alamouti's scheme, one has two virtual users for each user if the information symbols are real valued. The previously proposed code-constrained IFC-based detector is modified to detect a given virtual-user signal. The original user signal can then be recovered from the associated detected virtual user signals obtained by running two code-constrained IFC-based detectors in parallel. We also propose a novel approach combining the code-constrained IFC and a penalty function to simultaneously extract the two virtual user signals associated with a given user. Global minima of the proposed cost functions are analyzed. An illustrative simulation example is presented.